PRODUCT DEVELOPMENT TO INCREASE CUSTOMER’S SATISFACTION AT THE SME OF SUSHI BIZKID - Riani, Rika Triani; Mathory, Eljihad Akbari Syukriah (President University, 2024)
Indonesia's culinary industry has great potential to support economic growth. Entrepreneurs are required to be able to compete, one of which is by developing products such as determining quality, shape, attractiveness, size, packaging, and other aspects that are used as part of product development. Sushi Bizkid is one of the (SME) engaged in Japanese food culinary. Sushi Bizkid uses plain packaging and plastic mica to be used in takeaway orders, besides that, the lack of information and attractive elements on the packaging makes consumers give negative comments on online food applications. Packaging design containing product-related information can create strong branding for a product so that consumers can assume that the business intense to pays attention to consumer convenience. The purpose of this study is to create a product packaging design to increase customer satisfaction at (SME) Sushi Bizkid. This research method uses descriptive qualitative data collection methods through observation, interviews, and documentation. The results of this study are product development through packaging carried out with six stages of product development. Eight indicators need to be considered, namely performance, producing packaging that has performance because it has been able to meet consumer expectations related to identity and product information. Specialty, showing that the current packaging is unique in terms of visualization or packaging appearance. Reliability, packaging against shocks during product delivery. Serviceability is seen from the packaging service that keeps the product from damage and air space in the packaging. From these results product development through packaging can provide an increase in customer satisfaction.